Evaluation of learning in physical education: A bibliometric analysis and future trends - Hadiwinarto; Gheorghe Balint; Feby Elra Perdima (UIR Press, 2022)
This study analyzes academic research published in Scopus on the evaluation of physical education learning. This study focuses on the following research questions: (1) How is the productivity of educational evaluation publications in physical education developed using the Scopus database? (2) What are the most influential journals, authors, and articles in the field of educational evaluation in physical education learning? (3) What are the keywords that often appear in the field of educational evaluation in physical education learning in the Scopus database?. The search results show that research is